Kesiapan Madrasah Menyongsong Otonomi Daerah di Kabupaten Situbondo: The Readiness of Madrasahs in Facing Regional Autonomy in Situbondo Regency - Soebahar, Abd. Halim (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
The implementation of regional autonomy in Indonesia requires a fundamental transformation of madrasah education to remain relevant and adaptive. This study examines the readiness of madrasah in Situbondo Regency to face regional autonomy, focusing on suprastructure, infrastructure, financial management, and curriculum. A qualitative approach was employed, using in-depth interviews, non-participant observation, documentation, and focus group discussions with madrasah heads, foundation administrators, and government officials from six state and thirty-two private madrasah. The findings reveal that madrasah have not yet developed adequate capacity and capability to welcome regional autonomy. While some progress exists in certain areas, most madrasah lack sufficient human resources, functional organizational infrastructure, accountable financial systems, and curricula oriented toward local excellence and stakeholder needs. The study concludes that madrasah require systematic empowerment through training in database management, school-based quality improvement, leadership, and financial administration. It is recommended that the local government and the Ministry of Religious Affairs facilitate regrouping or mergers of non-viable madrasah as a strategic, persuasive measure to ensure sustainability and accountability. Pelaksanaan otonomi daerah di Indonesia menuntut transformasi mendasar pendidikan madrasah agar tetap relevan dan adaptif. Penelitian ini bertujuan mengkaji kesiapan madrasah di Kabupaten Situbondo menyongsong otonomi daerah dengan fokus pada suprastruktur, infrastruktur, pembiayaan, dan kurikulum. Pendekatan kualitatif digunakan melalui wawancara mendalam, observasi nonpartisipan, dokumentasi, dan diskusi kelompok terarah yang melibatkan kepala madrasah, pengurus yayasan, serta pejabat pemerintah dari enam madrasah negeri dan tiga puluh dua swasta. Temuan menunjukkan bahwa madrasah belum memiliki kapasitas dan kemampuan memadai dalam menyongsong otonomi daerah. Meskipun terdapat kemajuan pada sebagian aspek, sebagian besar madrasah masih kekurangan sumber daya manusia berkualitas, infrastruktur organisasi yang fungsional, sistem pembiayaan akuntabel, serta kurikulum yang berorientasi pada keunggulan lokal dan kebutuhan pemangku kepentingan. Penelitian menyimpulkan bahwa madrasah memerlukan pemberdayaan sistematis melalui pelatihan manajemen data, peningkatan mutu berbasis madrasah, kepemimpinan, dan administrasi keuangan. Pemerintah daerah dan Departemen Agama direkomendasikan memfasilitasi pengelompokan ulang atau merger madrasah yang tidak layak sebagai langkah persuasif strategis demi keberlanjutan dan akuntabilitas.